School Strategies in Shaping Environmental Care Behavior in Students Through the Implementation of the No Smoking Area (KTR) Policy - Silaban*, Carolus Tarman; Nurhadi, Nurhadi; Pudyastuti, Septina Galih (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to determine the school's strategy in forming environmentally caring behavior in students through the No-Smoking Area policy. The research method used is descriptive method with a qualitative approach. Sample selection used a purposive sampling technique where the researcher chose informants, namely the principal, deputy principal for student affairs, guidance and counseling teacher, homeroom teacher, and 5 students. Data collection techniques were carried out by in-depth interviews, observation and documentation. The research was analyzed using an interactive analysis model by Miles Huberman. The conclusions obtained in this research are the role of the school in overcoming student smoking behavior is carried out by the school principal, deputy head of student affairs, counseling teacher, and homeroom teacher. There are still students who carry out smoking activities outside the school environment during study hours because the guarding and supervision at the connecting gates between school buildings is not optimal, the school's supervision of students outside the school environment is limited, and outside the school's responsibility and the student's family backgrounds are different. It is also an obstacle for schools to cooperate with parents of students.